What's in the Stomach Is Used to Carry What's on the Head: An Ethnographic Exploration of Food Metaphors in Efik Proverbs. (March 2019) - Mensah, Eyo Offiong; Eni, Rosemary Arikpo
Food and foodways are essential components of the Efik biocultural system, as the Efik people of Southern Cross River State, Southeastern Nigeria, are famous for their rich dietary history and cuisine tradition. Food and foodways are, therefore, quintessential aspects of the Efik cultural history and social structure, which are intergenerational. This article explores the use of food symbolisms (embedded in rich metaphors) in Efik proverbs, which are perceptual frameworks or conceptual grids that highlight fundamental cultural values and mores as well as reinforce and instill acceptable social behavior. The study is rooted in the Afrocentric paradigm, which re-asserts the interpretation of Efik proverbs based on African values, perspectives, and narratives, and adds relevant ontological and epistemological analytic dimensions in operationalizing the collective and contextual understanding of Efik (African) proverbs. In this context, the Efik view the world through the lens of food, exploring the role of food and eating correlates as means of addressing their society's psychodynamic challenges, which paradoxically are not about food.